Assessment of MW-mile method for pricing transmission services: a negative flow-sharing approach - Lo, K. L.; Hassan, M. Y.; Jovanovic, S. (The Institution of Engineering and Technology, 2007)
A negative flow-sharing approach to allocate transmission transaction charges among users of transmission services is proposed. The approach uses the properties of the MW-mile method but takes into account the economic benefits of both trading parties by analysing their shares in negative power flow or counterflow. This approach is incorporated with the justified distribution factor for power flow tracing purposes. Two case studies based on a 5-bus system and an IEEE 14-bus system are used to illustrate the proposed approach. The results show that the proposed approach has merit over the traditional MW-mile approaches in the context of revenue reconciliation of transmission services, regardless of transaction arrangements and locations. The profit-sharing concept introduced here provides a better economic signal in allocating charges for counterflows, which could benefit trading parties. 1 Introduction The electric utility industry in many countries has been deregulated to further increase its competitiveness and efficiency and to reduce the cost of power generation, transmission and distribution. With deregulation, generation, transmission and distribution would be in different companies and their interactions would be based on purely commercial bases. As a result, a transmission company plays a major role in determining the charges for wheeling transactions. In the past, wheeling transactions have accounted for a small portion of the overall transmission network capacity usage. However, recent trends towards unbundling of electric services have resulted in renewed interest in pricing of transmission services, particularly as it relates to wheeling transactions [1]. Many methods have been used or proposed to evaluate the costs of transmission transactions or the so-called wheeling transactions. Most methods attempt at least two basic measurements: the amount of transmission capacity used and the per-unit cost of transmission capacity [2]. These methods can be classified into one of these categories: embedded cost and incremental or marginal cost. These categories have been discussed by some authors [2–5] and show their ability to provide reasonable economic costs. Among these methods, the embedded cost methods are